Analysis Of Implementation Of Local Government Financial Accounting Systems In Improving The Quality Of Local Government Financial Reports In Parepare City - Sariana Damis; Husnun Fadhilah (Journal AK-99, 2023)
This study aims to determine the application of the local government ﬁnancial accounting system in improving the quality of ﬁnancial reports at the BKD Oﬃce in Parepare City and the ﬁnancial reports from the BKD Oﬃce in Pare-Pare City have quality according to the law. No. 71 of 2010. This study used a qualitative descriptive study, the technique of determining the informants in this study used a purposive sampling technique, while the data collection techniques used in this study were interviews and documentation. The sample in this study is 5 people who are involved in the accountability of ﬁnancial report management. Data analysis techniques in this study used data collection analysis. The implementation of the Regional Financial Accounting System carried out by the BKD Oﬃce of the City of Parepare has been good as well as the output it produces, namely the Financial Report of the City of Parepare, implementation in the ﬁeld that those who input or manage the system are carried out by staﬀ in the ﬁeld of Accounting and Financial Reporting. The presentation of ﬁnancial reports at the BKD Oﬃce of Parepare City has fulﬁlled the characteristics of quality government ﬁnancial reports that have been listed in PP No.71 of 2010, including namely, reliable, relevant, comparable and understandable.